Upaya Pencegahan Infeksi Saluran Pernafasan melalui Edukasi Vaksinasi Secara Daring - Kambira, Pretty Falena Atmanda; Irawan, Alvin; Noviani, Lusy (Prima Abdika: Jurnal Pengabdian Masyarakat, 2024)
Pneumonia, a severe respiratory disease, can have deadly consequences. Increased air pollution in Jakarta can increase the risk of respiratory tract diseases, including Pneumonia. The risk of Pneumonia infection in adults can be reduced by vaccination. The Pharmacy Department of the Atma Jaya Catholic University of Indonesia held an in-depth seminar on Pneumonia and vaccination to provide information and invite all people to understand the urgency of vaccination. Educational activities are conducted as online seminars using a video conferencing platform. Two speakers gave interactively educational information about Pneumonia and vaccination, and more than 60 people attended the seminar. Demographic data on participants shows that the gender of most participants was female, the age of most participants was 26-45 years old, and the education level of most participants was university level. Of the participants who attended, as many as 63.7% had never been vaccinated against Pneumonia, and 68.1% were willing to be vaccinated against Pneumonia. In conclusion, this seminar successfully increased the knowledge and awareness of the public about Pneumonia and vaccination.